Data Security Analysis Using Virtual Ridgeback in Network Forensics - Firmansyah Firmansyah; Yusuf Hendra Pratama; Bayu Wibisana (Universitas Islam Al-Azhar Mataram, 2023)
Recorded two hospitals in Jakarta were hit by cyberattacks which caused patient data in hospital computer networks to be inaccessible. Symantec is an American company that manufactures data security software, according to Symantec's report entitled Internet Security Threat Report Volume 24 which was released in February 2019 then, in 2018, as much as 2.23%, cyberattacks in the global arena occur in Indonesia, increasing from the previous year, namely 1.67%. Meanwhile, the figure also places Indonesia in fifth place as the country that has the most cyber threats in 2018. It can operate on physical networks or on virtual networks. The only requirement is that the Ridgeback installation has access to the layer 2 network layer. Ridgeback Network Defence makes resistance to intruders using interactive defences and causes intruders to spend unnecessary resources. Interactive Defence is an advanced disguise and fraud capability designed to ensnare intruders in several ways, namely by managing billions of feeds in the network that can trigger intruder responses, affect intruder behavior so that they are easier to detect, and block access to protected network services without revealing that service has been blocked. This research is expected to create a control center by adopting a Software Defined Network (SDN) so that it can capture intruders and get data about the attack, which can be used as evidence in the process of investigating network forensics quickly and precisely.